The Effect of Diboracy (Digital Book Containing Scientific Literacy) in Reducing Misconceptions on Newton’s Law of Gravity - Sasmita, Fauzia Dwi; Arifuddin, Muhammad; Mahtari, Saiyidah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2020)
The low utilization of technology and scientific literacy skills lacking in the classroomsremaina major problem in the learning and teaching process, specifically in influencing students' conceptual understanding. This research aims to analyze the effect of Diboracy (Digital Book Contained Scientific Literacy) in reducing misconceptions in Newton's law of gravity. This research uses experimentalresearch design with one group pre-test-post-test conductedon research subjects which were selected through random sampling technique. The sum of the research subjects include 38 students. The data instruments include tests and non-tests instruments. The test distributed is in the form of multiple choice questions equipped with CRI to measure the misconceptions, while the non-test assessmenttakes form of questionnaires to determine students’ responses to Diboracy. Data analysis was performed through t-test on student learning outcomes and the students’ questionnaire responseswhich resulted in the average percentages. Based on the analysis, it can be concluded that: (1) there is an effect in reducing students’ misconceptions when Diboracy is implemented, specifically regarding Newton's law of gravity; (2) students give better responses to Diboracy than textbooks.